If \[x+1\] is a factor of \[2{{x}^{3}}+a{{x}^{2}}+2bx+1\] ,then find the value of a and b given that \[2a-3b=4\]
Answer
Verified
483.3k+ views
Hint: Let there be any cubic equation as \[a{{x}^{3}}+b{{x}^{2}}+cx+d=0\] which has three roots as \[\alpha ,\beta ,\gamma \]
So we can write this cubic equation as \[a(x-\alpha )(x-\beta )(x-\gamma )=0\], Now we can also say that \[(x-\alpha ),(x-\beta )and(x-\gamma )\] are the factors of cubic equation \[a{{x}^{3}}+b{{x}^{2}}+cx+d=0\] . We will obtain an equation in terms of a and b substituting factor which is x+1=0 or x=-1 in the given equation. We have already been given another equation in a and b, so now using elimination method, we can compute values of a and b.
Complete step-by-step answer:
In the question we are given a cubic equation as \[2{{x}^{3}}+a{{x}^{2}}+2bx+1=0\] which has a factor \[x+1\]
Assuming the roots are \[\alpha ,\beta ,\gamma \] so we can write our cubic equation as
\[2(x-\alpha )(x-\beta )(x-\gamma )=0\]
And factors of this equation will be \[(x-\alpha ),(x-\beta )and(x-\gamma )\]
But one factor given as \[x+1\]
So, replacing \[(x-\alpha )\] with \[x+1\]
Now our equation can be written as \[2(x+1)(x-\beta )(x-\gamma )=0\]
Looking this carefully if we make \[(x+1)=0\] then this cubic equation will become 0
It means \[(x+1)=0\] gives \[x=-1\] is a solution of this cubic equation
putting \[x=-1\] in equation \[2{{x}^{3}}+a{{x}^{2}}+2bx+1\] will make this equation 0
\[2{{(-1)}^{3}}+a{{(-1)}^{2}}+2b(-1)+1=0\]
\[\to (-2+a-2b+1)=0\]
On solving gives
\[a-2b=1.......(1)\]
Now \[a\]and \[b\]are unknown
But in the question, we are given an equation \[2a-3b=4.......(2)\]
So, we have 2 equation and 2 variables \[a\] and \[b\]
We can calculate them but elimination method
So first we eliminate \[a\]
Multiplying the equation (1) with 2
Now equation (1) will look like
\[2a-4b=2.........(3)\]
On subtracting equation (3) from equation (2), we get
\[2a-3b-(2a-4b)=4-2\]
\[2a-3b-2a+4b=2\]
\[b=2\]
Now we get \[b=2\] so we can put this value in equation (1) to get the value of \[a\]
Equation (1) \[a-2b=1\]
\[a-2(2)=1\]
\[a=5\]
Hence, we get the value \[a=5\] and \[b=2\]
Note: In this question students can make mistakes, by taking its root as 1 and not -1. This question is very basic; you just need to solve equations carefully. You can also calculate the values of \[a\] and \[b\] by substitution method.
Like we are given these two equations so we find value of \[a\] from equation (1) and put it in equation (2)
\[a-2b=1.......(1)\] \[2a-3b=4.......(2)\]
\[a=1+2b\] from equation (1)
Putting value of \[a\] into equation (2)
We get
\[2(1+2b)-3b=4\]
\[\to 2+4b-3b=4\]
\[\to 2+4b-3b=4\]
\[\to b=2\]
And we have \[a=1+2b\] so putting value \[b=2\]
\[\to a=5\]
So we can write this cubic equation as \[a(x-\alpha )(x-\beta )(x-\gamma )=0\], Now we can also say that \[(x-\alpha ),(x-\beta )and(x-\gamma )\] are the factors of cubic equation \[a{{x}^{3}}+b{{x}^{2}}+cx+d=0\] . We will obtain an equation in terms of a and b substituting factor which is x+1=0 or x=-1 in the given equation. We have already been given another equation in a and b, so now using elimination method, we can compute values of a and b.
Complete step-by-step answer:
In the question we are given a cubic equation as \[2{{x}^{3}}+a{{x}^{2}}+2bx+1=0\] which has a factor \[x+1\]
Assuming the roots are \[\alpha ,\beta ,\gamma \] so we can write our cubic equation as
\[2(x-\alpha )(x-\beta )(x-\gamma )=0\]
And factors of this equation will be \[(x-\alpha ),(x-\beta )and(x-\gamma )\]
But one factor given as \[x+1\]
So, replacing \[(x-\alpha )\] with \[x+1\]
Now our equation can be written as \[2(x+1)(x-\beta )(x-\gamma )=0\]
Looking this carefully if we make \[(x+1)=0\] then this cubic equation will become 0
It means \[(x+1)=0\] gives \[x=-1\] is a solution of this cubic equation
putting \[x=-1\] in equation \[2{{x}^{3}}+a{{x}^{2}}+2bx+1\] will make this equation 0
\[2{{(-1)}^{3}}+a{{(-1)}^{2}}+2b(-1)+1=0\]
\[\to (-2+a-2b+1)=0\]
On solving gives
\[a-2b=1.......(1)\]
Now \[a\]and \[b\]are unknown
But in the question, we are given an equation \[2a-3b=4.......(2)\]
So, we have 2 equation and 2 variables \[a\] and \[b\]
We can calculate them but elimination method
So first we eliminate \[a\]
Multiplying the equation (1) with 2
Now equation (1) will look like
\[2a-4b=2.........(3)\]
On subtracting equation (3) from equation (2), we get
\[2a-3b-(2a-4b)=4-2\]
\[2a-3b-2a+4b=2\]
\[b=2\]
Now we get \[b=2\] so we can put this value in equation (1) to get the value of \[a\]
Equation (1) \[a-2b=1\]
\[a-2(2)=1\]
\[a=5\]
Hence, we get the value \[a=5\] and \[b=2\]
Note: In this question students can make mistakes, by taking its root as 1 and not -1. This question is very basic; you just need to solve equations carefully. You can also calculate the values of \[a\] and \[b\] by substitution method.
Like we are given these two equations so we find value of \[a\] from equation (1) and put it in equation (2)
\[a-2b=1.......(1)\] \[2a-3b=4.......(2)\]
\[a=1+2b\] from equation (1)
Putting value of \[a\] into equation (2)
We get
\[2(1+2b)-3b=4\]
\[\to 2+4b-3b=4\]
\[\to 2+4b-3b=4\]
\[\to b=2\]
And we have \[a=1+2b\] so putting value \[b=2\]
\[\to a=5\]
Recently Updated Pages
Master Class 9 General Knowledge: Engaging Questions & Answers for Success
Master Class 9 English: Engaging Questions & Answers for Success
Master Class 9 Science: Engaging Questions & Answers for Success
Master Class 9 Social Science: Engaging Questions & Answers for Success
Master Class 9 Maths: Engaging Questions & Answers for Success
Class 9 Question and Answer - Your Ultimate Solutions Guide
Trending doubts
Fill the blanks with the suitable prepositions 1 The class 9 english CBSE
How do you graph the function fx 4x class 9 maths CBSE
Name the states which share their boundary with Indias class 9 social science CBSE
Difference Between Plant Cell and Animal Cell
What is pollution? How many types of pollution? Define it
What is the color of ferrous sulphate crystals? How does this color change after heating? Name the products formed on strongly heating ferrous sulphate crystals. What type of chemical reaction occurs in this type of change.